Distribusi Frekuensi Ukuran Lebar Karapas dan Berat Kepiting Bakau (Scylla serrataforskal) dengan Alat Tangkap Bubu Lipat di Perairan Kabupaten Teluk Bintuni, Papua Barat - Franklyn Hoek; Abudarda Razak; Misbah Sururi; Maximus Yampapi (Jurnal Airaha, 2015)
The aim of research was to analyze the distribution of width-weight carapaces relationship, and growth pattern mud crab (Scylla serrata) are expected for the management. The object are mud crab in Distrik Bintuni West-Papua waters during three month. Analysis with SPSS programme version 19th. Relationship of width-weight carapace used by regression statistic. The result shown frequency distribution width-weight relationship of males and females were not significant. The confidence limit of frequency distribution union width-carapace males and females were 12.5 to 12.3 cm, while the weight male crab 496.7 to 520.1 g, and weight of female crab 366,2 to 381 g. Males crab have allometriks positive growth pattern (b > 3), and female crabs have allometriks negative ( b <3). The female mud crab (Scylla serrata) for three month (July, August, September) was indicated growning of the maturity process.